Supramolecular Tadalafil Nanovaccine for Cancer Immunotherapy by Alleviating Myeloid‐Derived Suppressor Cells and Heightening Immunogenicity. Issue 6 (13th May 2021) - Zhang, Tian; Xiong, Honggang; Ma, Xianbin; Gao, Yuan; Xue, Peng; Kang, Yuejun; Sun, Zhi‐Jun; Xu, Zhigang
Abstract: Tumor‐induced immune suppression mediated by myeloid‐derived suppressor cells (MDSCs) and insufficient immunogenicity are two major factors for the poor overall response rate to the immune checkpoint blockade (ICB). Here, a tumor microenvironment responsive nanoprodrug (FIT nanoparticles) is presented for co‐delivering tadalafil (TAD) and indocyanine green (ICG) photosensitizer to simultaneously targeting intratumor MDSCs and amplifying tumor immunogenicity. The resulting nanoprodrug shows high drug loading (nearly 100%), tumor‐specific release, and robust therapeutic efficacy by virtue of promoting immunogenic cell death (ICD) induction and alleviation of MDSCs for augmenting the photothermal immunotherapy. In an in vivo colon tumor model, the released TAD in the tumor can effectively ameliorate MDSCs immunosuppressive activity, while the photosensitizer ICG is capable of inducing ICD to promote sufficient dendritic cells maturation and T cell infiltration. The results reported here may provide a superior candidate of adjuvants for strengthening immune response and ICB efficacy. Abstract : Tadalafil‐based nanoparticles with high drug loading, deep tumor depth‐penetration, and adequate therapeutic performance are reported for potentiating cancer immunotherapy by inducing immunogenic cell death effect and alleviating myeloid‐derived suppressor cells. This strategy would provide an excellent example for the design of a Tadalafil‐based immunotherapeutic system, furthest responding to these bottlenecks in the clinical transformation of cancer nanomedicine.